The revolutionary life of Freda Bedi: British feminist, Indian nationalist, Buddhist nun - Mackenzie, Vicki (Shambhala, 2017)
"A fascinating biography of Freda Bedi, an English woman who broke all the rules of gender, race, and religious background to become both a revolutionary in the fight for Indian independence and then a Buddhist icon. Freda Bedi (1911-1977) was one of the most remarkable and iconoclastic figures in Buddhism's movement to the West. Born in England, educated at Oxford, and married to a Sikh, she became a major force both in shaping modern-day Buddhism and Indian history. In her life she had many roles--political freedom fighter, spiritual seeker, scholar, professor, journalist, author, social worker, wife, and mother of four children (one of whom is a well-known actor). Vicki MacKenzie's lively biography captures what a trailblazer Bedi was in both the secular and spiritual realms. She studied meditation with Burmese meditation masters. She was the first English woman to be accepted by Gandhi into his elite band of Satyagrahi, delivering rousing speeches to thousands of Indians urging them to revolt, and then was imprisoned for subversion. She was asked by Nehru to help resettle Tibetan refugees, and she aided the Dalai Lama when he went into exile. Bedi established a school for young Tibetan lamas and also a nunnery, which still exists, to provide nuns equal religious opportunities. She was also the first woman, of any nationality, to receive the full Bikshuni ordination, making her the highest-ranking Tibetan Buddhist nun in India. MacKenzie, a well-known journalist in Britain, has forty years of experience writing about Buddhism in the West. For this book, she traced Bedi's footsteps and conducted many in-depth interviews with those who knew her, including friends, family, government officials, lamas, and nuns. She also drew heavily from Bedi's own writings, diaries, and recordings--all provided by Bedi's family--and the book includes many photographs"--